Special Issue: “Post-COVID-19 Syndrome” - Rüdiger E. Scharf (Viruses)
On 30 January 2020, the World Health Organization declared COVID-19 a Public Health Emergency of International Concern (PHEIC)—the highest WHO warning level [...]